Efficacy of teaching medical students by problem-based learning method - O. K. Коloskova; T. M. Bilous; G. A. Bilyk; S. S. Kaliyeva; V. P. Riklefs; G. Z. Abakassova; A. Z. Muratova (Kazimierz Wielki University, 2018)
To determine and analyze the evaluate efficacy of teaching senior students of medical faculties at Universities in terms of avoiding medical errors in pediatrics. Students studied according to problem based learning method while learning the subject "Pediatrics" within the framework of ERASMUS+ ТАМЕ project. Therefore, students were distributed into three groups: students, who learnt pediatrics by branch case method, students, who studied by problem-based learning method and linear cases method in particular and students, who studied by the traditional classical scheme of teaching pediatrics. The compiled questionnaire consisted of questions including: questions the subject of cases, tangent questions, they were not included into cases and control questions. The analysis of questionnaire of students showed that the best result (in percent of right answers) was seen in I group; its representatives studied by branch cases (42,0% Ukrainian and 43,2% Kazakhstan). The lowest percentage of right answers (37,6%) was determined in the control ІІІ group (41,9% in Kazakhstan), and the results of the group with linear cases was 40,6% of right answers (36,5% in Kazakhstan). Thus, problem-based learning considerably stimulates motivation of students to learning and promotes better efficacy of the whole educational process. Students who study according to problem-based learning method as compared to those who study according to the traditional methods demonstrate better results by the number of right answers given to tests.